2016
DOI: 10.1139/cjps-2014-0348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilization on camelina seed yield, yield components, and downy mildew infection

Abstract: Camelina [Camelina sativa (L.) Crantz] has potential in aquaculture, livestock feed production, and the biofuel industry. It is necessary to determine the appropriate production technology for the newly introduced crop under different environmental conditions. The objective of this 2-year study was to measure the response of five camelina genotypes in terms of seed yield, yield components, and disease incidence to applied nitrogen (N) at multiple sites in the Maritime provinces of eastern Canada. The factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
5
17
1
Order By: Relevance
“…In treatments with seeding rates of 200, 300, and 400 seeds m −2 , the 1,000 seed weight of seeds supplied with 50 kg N ha − 1 was determined at 1.02, 0.98, and 0.87 g, respectively, and the 1,000 seed weight of camelina fertilized with 100 kg N ha − 1 was determined at 1.13, 1.00, and 0.93 g, respectively. An increase in the 1,000 seed weight of camelina in response to increasing nitrogen rates from 0 to 200 kg N ha − 1 was also reported by Jiang and Caldwell (). However, Solis, Vidal, Paulino, Johnson, and Berti () found that nitrogen fertilization had no significant effect on 1,000 seed weight.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In treatments with seeding rates of 200, 300, and 400 seeds m −2 , the 1,000 seed weight of seeds supplied with 50 kg N ha − 1 was determined at 1.02, 0.98, and 0.87 g, respectively, and the 1,000 seed weight of camelina fertilized with 100 kg N ha − 1 was determined at 1.13, 1.00, and 0.93 g, respectively. An increase in the 1,000 seed weight of camelina in response to increasing nitrogen rates from 0 to 200 kg N ha − 1 was also reported by Jiang and Caldwell (). However, Solis, Vidal, Paulino, Johnson, and Berti () found that nitrogen fertilization had no significant effect on 1,000 seed weight.…”
Section: Resultssupporting
confidence: 79%
“…The most appropriaterate of nitrogen fertilizer has been estimated at 60-80 kg N ha −1 in Atlantic Canada (Urbaniak, Caldwell, Zheljazkov, Lada, & Luan, 2008) and at 120-160 kg N ha −1 in eastern Canada (Jiang, Caldwell, Falk, Lada, & MacDonald, 2013); whereas in the Canadian prairies, the highest yields were reported in response to a fertilizer rate of 170 kg N ha −1 (Malhi et al, 2014). The results of research studies analyzing the effects of different rates of nitrogen fertilizer on camelina yields are ambiguous and often contradictory (Jiang & Caldwell, 2016), which could be attributed to strong yield compensation mechanisms in different environments, such as the increase in the number of seeds per silique or the increase in seed weight (Mason & Guillen-Portal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, based on N source, rate, and cultivar, grain production of camelina ranged from 534 to 1,010 kg/ha and falls within the range of 127 to 3,303 kg/ha reported from studies in several countries across the globe (Czarnik, Jarecki, & Bobrecka‐Jamro, ; Malhi et al, ; Sintim et al, ; Solis, Vidal, Paulino, Johnson, & Berti, ). Based on camelina grain yield response in this study, applying N beyond 80 kg/ha did not result in a significant increase in grain yield but other studies have reported a wide variation in camelina grain yield response to N rates, ranging from 56 to 200 kg N ha ‐1 (Jiang & Caldwell, ; Jiang et al, ; Sintim et al, ; Solis et al, ). This wide range of N required for optimum grain production is heavily dependent on genotype used, environmental conditions, and management approaches utilized in growing grain crops like camelina (e.g., Setiyono et al, ).…”
Section: Discussionmentioning
confidence: 53%
“…Year 2 (2017) 2015; Solis, Vidal, Paulino, Johnson, & Berti, 2013). Based on camelina grain yield response in this study, applying N beyond 80 kg/ha did not result in a significant increase in grain yield but other studies have reported a wide variation in camelina grain yield response to N rates, ranging from 56 to 200 kg N ha -1 (Jiang & Caldwell, 2016;Jiang et al, 2013;Sintim et al, 2015;Solis et al, 2013). This wide range of N required for optimum grain production is heavily dependent on genotype used, environmental conditions, and management approaches utilized in growing grain crops like camelina (e.g., Setiyono et al, 2011).…”
Section: Spadmentioning
confidence: 50%
“…An important agricultural treatment is also a mineral fertilization. Like other cultivated plants in the family Brassicaceae (Brassicaceae Burnett) false flax strongly respond to nitrogen fertilization (Solis et al, 2013;Jiang and Caldwell, 2016;Waraich et al, 2017).…”
Section: Introductionmentioning
confidence: 99%